Interações planta-polinizador e planta-florívoros no Cerrado: explorando as dependências da densidade - Leite, Ludimila Juliele Carvalho (2023)
The density of plant species within a population has been discussed as one of the factors with significant effects on herbivory and pollination interactions. Regarding herbivory, denser plant populations are hindered by the facilitation of herbivore encounters, referred to as negative density dependence, reported by Janzen and Connell as one of the mechanisms for maintaining tropical diversity. On the other hand, for pollination, this facilitation of flower encounters by pollinators is advantageous for reproductive success and population growth. However, floral herbivores use the same flower cues to locate them, just like pollinators do. Additionally, fruiting analysis depends not only on plant densities in the field but also on the reproductive system type of each species. The objective of this study was to investigate the reproduction of Peixotoa tomentosa A. Juss. and Byrsonima intermedia A. Juss. (Malpighiaceae), considering the effects of density variations on pollinator attractiveness and florivore action. The main hypothesis was that population density affects fruit production. For this purpose, two treatments were conducted, with individuals grouped (N=30) and isolated (N=30) in a Brazilian savanna area. Flowers were marked and monitored to record fruiting and controlled pollinations were performed to identify the prevalent reproductive system of each species. Focal observations were conducted to identify the main floral visitors and determine the pollinators, as well as investigate if visitation rates were affected by the density of conspecific plants. Flowers were marked and collected for analysis of total area and area lost due to florivore action, while other flowers were bagged the day after anthesis to determine if post-pollination florivore action affects fruiting in grouped plants. Our results demonstrate that fruiting in both species was positively dependent on density. Peixotoa tomentosa was characterized as a self-compatible and agamosperm species, while B. intermedia is self-incompatible and exclusively depends on pollinator action for reproduction. Floral visitation rates varied only in B. intermedia, where grouped plants received more visits than isolated ones. Bees considered potential pollinators were only observed visiting B. intermedia flowers, likely due to a long time after environmental disturbances caused by frosts and fires. Additionally, more flowers from isolated P. tomentosa individuals were damaged by florivores, while in B. intermedia, there were no differences in the number of attacked flowers, or the area consumed by them in both treatments. Post pollination damage did not cause a difference in fruiting for P. tomentosa, but it did for B. intermedia, possibly due to some detail in the manipulation of inflorescences. The results obtained in this study demonstrate that plant-pollinator and plant-florivore interactions are conditioned by plant densities in natural populations. Increases in pollinator-mediated fruiting and damage due to florivory are influenced by the attraction of these agents, driven by multiplied floral displays in denser populations or by the size and quantity of flowers in isolated individuals.